2023
DOI: 10.1108/tlo-10-2022-0118
|View full text |Cite
|
Sign up to set email alerts
|

High-performance work system and learning orientation in offline, online, and hybrid workplaces: the mediating role of affective commitment

Rohit Yadav,
Mohit Yadav,
Nitin Simha Vihari

Abstract: Purpose The present study primarily aims to investigate the role of the high-performance work system (HPWS) in shaping learning orientation (LO). Moreover, the study delves into the examination of affective commitment's (AC) role as a mediator. Additionally, the research extends to exploring the potential moderating impact of workplace settings, specifically offline, online and hybrid workplaces, on the mediated relationship. Design/methodology/approach The model has been tested on 360 respondents from the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…When employees have high levels of affective commitment or emotional bond to the organization, investing in high-performance work systems can increase employees' orientation to learning. Yadav et al (2024) found that this is even more pronounced in the hybrid workplace than in purely offline work. High-performing work systems include training and development processes that show employees that they are valued and supported in their work, which contributes to their sense of affective commitment to the organization.…”
Section: Challenges Of Developing a Learning Culturementioning
confidence: 92%
See 1 more Smart Citation
“…When employees have high levels of affective commitment or emotional bond to the organization, investing in high-performance work systems can increase employees' orientation to learning. Yadav et al (2024) found that this is even more pronounced in the hybrid workplace than in purely offline work. High-performing work systems include training and development processes that show employees that they are valued and supported in their work, which contributes to their sense of affective commitment to the organization.…”
Section: Challenges Of Developing a Learning Culturementioning
confidence: 92%
“…When employees have a high level of affective commitment or emotional attachment to the organization, investing in high-performance work systems can increase employees' learning orientation. Yadav, Yadav, & Vihari (2024) found that this is even more pronounced in the hybrid workplace than in purely offline work. Oppong Peprah (2024) decided to investigate the prevalence of this form of work and employees' attitudes toward it in the Greater Accra region of Ghana.…”
mentioning
confidence: 92%
“…Searching for an object is a common task in indoor environments. While there is a rich body of work dedicated to the object navigation task [13], [16], [17], [18], [12], [19], most are limited in a close-set of objects. In response, many researchers study the more realistic open-vocabulary object navigation task.…”
Section: A Open-vocabulary Object Navigationmentioning
confidence: 99%
“…By integrating organizational strategies with HR strategies, it generates a synergistic effect that enhances performance. The article titled "High-Performance Work System and Learning Orientation in Offline, Online, and Hybrid Workplaces: The Mediating Role of Affective Commitment" authored by Yadav, Yadav, and Vihari (2023), investigated the role of the HPWS in shaping learning orientation by testing a model on 360 respondents from the IT sector in India. The results indicate that affective commitment mediates the relationship between HPWS and learning orientation.…”
mentioning
confidence: 99%